Expansion of The Meaning of The Word International in International Arbitration Decisions in Indonesia - Puspita, Lona (UNISKA LAW REVIEW, 2023)
An international arbitration award is a decision handed down by an arbitration institution or individual arbitrator outside the jurisdiction of the Republic of Indonesia, or a decision by an arbitration institution or individual arbitrator which according to the legal provisions of the Republic of Indonesia is considered an international arbitration award. From this understanding, it can be seen that Indonesia adheres to the territorial principle to determine whether an arbitration award is international or national. What about other foreign elements contained in an arbitration award, such as choice of law or choice of forum? The aim of this research is to find a new meaning for the word "International" in international arbitration decisions. The method used in this research is normative legal research. The research results state that the meaning of the word "international" in an international arbitration award should not only be territorial because the word international has a broader meaning which includes foreign elements contained in an arbitration award such as choice of law, choice of forum or choice of jurisdiction.